2020
DOI: 10.3389/fendo.2020.577650
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effect of High-Fat Diet on Glycerol Metabolism in Murine Adipose Tissue and Liver

Abstract: Obesity is associated with increased plasma glycerol levels. The coordinated regulation of glycerol channels in adipose tissue (AQP7) and the liver (AQP9) has been suggested as an important contributor to the pathophysiology of type-2-diabetes mellitus, as it would provide glycerol for hepatic synthesis of glucose and triglycerides. The regulation of AQP7 and AQP9 is influenced by sex. This study investigates the effect of a high-fat diet (HFD) on glycerol metabolism in mice and the influence of sex and GLP-1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
1
14
1
Order By: Relevance
“…These results are not consistent with a study using a cell model of NAFLD where silencing of AQP9 prevented or alleviated the degree of intracellular steatosis [103]. A work with male and female mice fed for 24 weeks with a high-fat diet showed that only males displayed liver steatosis without significant modification in AQP9 expression [81]. The originating factors and onset of the fatty liver disease, pathogenic pattern and gender of the studies subjects and animals should be take into account to appreciate the involvement of AQP9 in the disease.…”
Section: Metabolic Disorderscontrasting
confidence: 86%
See 1 more Smart Citation
“…These results are not consistent with a study using a cell model of NAFLD where silencing of AQP9 prevented or alleviated the degree of intracellular steatosis [103]. A work with male and female mice fed for 24 weeks with a high-fat diet showed that only males displayed liver steatosis without significant modification in AQP9 expression [81]. The originating factors and onset of the fatty liver disease, pathogenic pattern and gender of the studies subjects and animals should be take into account to appreciate the involvement of AQP9 in the disease.…”
Section: Metabolic Disorderscontrasting
confidence: 86%
“…In rat liver, the AQP9 expression is stronger in the pericentrolobular region of the hepatic lobule than in the periportal area [73,79]. Males exhibit higher hepatic expression of AQP9 than females both in rodents and human [22,80,81].…”
Section: Expression In Human and Rodentsmentioning
confidence: 92%
“…An analysis of the livers from the HFD-fed LKO mice revealed a significant increase in the hepatic expression of GK (a PPARγ gene target) compared with HFD control mice ( Figure 2, B and D , and Supplemental Figure 3F ). Previous studies have also demonstrated that HFD induces GK expression ( 19 ). Glycerol enters the liver primarily via aquaglyceroporins (AQPs), such as AQP3 and AQP9 ( Figure 2C and refs.…”
Section: Resultsmentioning
confidence: 89%
“…This intriguing down-regulation of AQP9 under lipid overload was suggested as a protective measure to reduce the influx of the glycerol and slow down the hepatic triacylglycerol accumulation [ [119] , [120] , [121] ]. Interestingly, despite a similar expression of hepatic AQP9 in both the women and men, women have a lower hepatic glycerol permeability, potentially explaining the lower incidence of NAFLD in women [ 122 ]. As aquaporin channel regulation was already confirmed in the case of AQP8 [ 12 ], a possible post-transcriptional modification -driven modulation of AQP9 glycerol permeability cannot be excluded.…”
Section: Possible Role Of Aqps “Metabolic Network” In Obesity-induced Systemic Insulin Resistancementioning
confidence: 99%
“…Moreover, no effect of HFD on the liver AQP9 and no association between the increasing hepatic steatosis and AQP9 levels were visible. Finally, there was no evidence of coordinated regulation of adipose tissue AQP7 and hepatic AQP9 [ 122 ]. Hopefully, this controversy will stimulate the scientific community to deepen the study of AQP7 and AQP9 relationship, also deploying the newest approaches.…”
Section: Possible Role Of Aqps “Metabolic Network” In Obesity-induced Systemic Insulin Resistancementioning
confidence: 99%